Pengaruh Lokasi, Keragaman Produk dan Store Layout terhadap Keputusan Pembelian pada Konsumen Moncheri Hijab di Balikpapan - Erika Yuniar; Dewi Sartika (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This study aims to analyze the partial and simultaneous influence of location, product diversity, and store layout on consumer purchasing decisions at Moncheri Hijab in Balikpapan. This research employed a quantitative approach using a survey method by distributing questionnaires to 170 respondents who were consumers of Moncheri Hijab in Balikpapan. The data analysis techniques used included validity testing, reliability testing, multiple linear regression analysis, t-test, and F-test. The results showed that partially, the location variable had a positive and significant effect on consumer purchasing decisions. Product diversity was also proven to have a positive and significant influence on purchasing decisions. Meanwhile, the store layout variable did not show a positive and significant effect on consumer purchasing decisions. However, simultaneously, the three variables, namely location, product diversity, and store layout, had a positive and significant influence on purchasing decisions among Moncheri Hijab consumers in Balikpapan. This study indicates that location and product diversity are the main considerations for consumers in making purchasing decisions, while store layout has not yet become a dominant factor influencing consumer purchasing decisions at Moncheri Hijab Balikpapan.